SELECT COMPANY BUSINESS STRATEGIES IN FULL OF UNCERTAINTY - Mikhail N. Konotopov (Статистика и экономика, 2016)
This article proposes an approach to the choice of the business strategies of the company in the conditions of complete market demand uncertainty. It is based on using the so-called strategic statistical games - market becomes the first player and the head of the organization, receiving the administrative decision, the second. Formed matrix losses of the company, the relevant combinations of possible states of a market demand and selected business strategies. To select the optimal business strategies, corresponding to the concrete possibilities of the company, Wald, Savage and Hurwitz rules are used.